Kinesio Taping (KT) dapat Menurunkan Nyeri Punggung Bawah Ibu Hamil - Elly, Nur -; Asepta, M; Wulandari, Dwi (Jurusan Kebidanan Poltekkes Kemenkes Padang, 2025)
Lower back pain is one of the most common complaints experienced by pregnant women in their third trimester. Pain can occur due to biomechanical and hormonal changes during pregnancy. Pain can disrupt comfort, mobility, and quality of life for pregnant women. Studies examining the effectiveness of kinesio taping to reduce back pain in pregnant women are still limited. This study aims to determine the effectiveness of kinesio taping in reducing the intensity of lower back pain in pregnant women in their third trimester. The research design used was a pre-experimental study with a one-group pretest-posttest approach. The study sample consisted of 46 pregnant women in their third trimester with complaints of lower back pain. The sample was obtained using consecutive sampling technique. The intervention consisted of installing kinesio taping on the mothers' lower backs for 7 days. Pain intensity was measured using the Numeric Rating Scale (NRS) before the intervention, on day 3, and day 7 after kinesio taping installation. Statistical analysis used the Friedman test to determine the difference in average pain scores between measurement times. The average pain scale before the intervention was 6.17. After the 3rd day, it decreased to 4.80, and on the 7th day it was 3.35, with a p-value of 0.000 (p < 0.05). The results showed a significant difference in the reduction of back pain based on the duration of kinesio tapping. Kinesio taping has been proven effective in reducing the intensity of lower back pain in pregnant women in the third trimester over time. Kinesio taping can be a safe and practical non-pharmacological therapy option to support maternal comfort during pregnancy. Keywords: kinesio taping; low back pain; third trimester of pregnancy.